The Fibonacci Hybrid Numbers - Szynal-Liana, Anetta; Wioch, Iwona (Utilitas Mathematica, 2019)
The hybrid numbers are a new type of numbers introduced in [8]. They generalize complex, hyperbolic and dual numbers. In this paper we consider the Fibonacci hybrid numbers and we derive some their properties using classical Fibonacci identities. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.